Coupled sandbar patterns and obliquely incident waves. Issue 3 (5th September 2013) - Price, T. D.; Castelle, B.; Ranasinghe, R.; Ruessink, B. G.
<x xml:space="preserve">Abstract</x> [1] In double sandbar systems, the alongshore variability in the inner bar often resembles that of the outer bar, suggesting that the outer bar acts as a morphological template for the inner bar. Earlier observations have indicated that this resemblance, also termed "coupling, " may take several forms. Here we apply a nonlinear 2DH morphodynamic model with time‐invariant forcing to show that the angle of wave incidence (θ) is crucial for the alongshore‐variable morphodynamic evolution of the inner bar, for a given crescentic outer bar. In contrast to previous modeling efforts of double‐barred systems, which mostly used highly idealized boundary conditions, we force our model with realistic hydrodynamics and bathymetrical data derived from video observations at the double‐barred Gold Coast, Australia. The results show that for small angles of wave incidence (θ<10°) over a crescentic outer‐bar, cell‐circulation patterns govern the flow at the inner bar, giving rise to rip channels that incise the inner bar at the locations of the landward perturbations in the outer bar (horns). On the other hand, for obliquely incident waves (θ=10°–20°) over a crescentic outer bar, the circulatory nature of the flow disappears and gives way to a meandering alongshore current. The offshore‐directed sections of this meandering alongshore current erode the inner‐bar downdrift of the outer‐bar horns, leading to landward perturbations of the inner bar that are coupled to the outer‐bar horns; an observed coupling type that had not been reproduced as yet. Oblique wave incidence thus proves to be crucial to the development of this type of sandbar coupling, as previously hypothesized from sandbar‐coupling observations at the Gold Coast. Additional simulations including tidal water level variations and bar depth variations demonstrate the robustness of our findings.